التوجيه النحوي بالحذف والزيادة في التراكيب الإسنادية في كتاب " مختصر في شواذ القرآن " لابن خالوية - مير، لبنى شكيل
Abu Abdullah Al-Hussein bin Ahmed bin Khalawayh is considered one of the greatest linguists who contributed to the science of Quranic readings, especially the shazah readings. Among his contributions is the book “Mukhtasar Fi Shawaz il Quran.” The researcher attempted to explain the shazah readings within a grammatical context. In view of the importance of the phenomenon of omission and increase in Qur’anic readings, the topic of omission and increase in predicate structures was chosen to reveal their manifestations and aspects. The research was based on the descriptive analytical method, focusing on the biography of Ibn Khalawayh, his grammatical method and the concepts of grammatical explanations, subject and predicate. Chapter 2 and 3 deal with the omission and the increase in the predicate structures - jumlah ismiyyah and jumlah fi’liyyah- in the shazah readings in contrast to mutilator readings. In each topic, the researcher presented and analysed the syntactic aspects of each of the shazah and mutilator readings to show the difference in meanings resulting from different syntactical structures. , during which several directions appear for each of the shazah readings, so the researcher compares them. Among the most important results of the study are: Firstly, the reason for Ibn Khalawayh's lack of fame in grammar was his new grammatical concept. He believed that language is taken by hearing (sama’), not by analogy (qiyas) and the predicate in the nominative sentence, if omitted, its taqdir is either prepositional phrase, or an adverb, or a noun. On the other hand, the predicate in the nominative predicate sentence if omitted, then its taqdir is either a pronoun or a noun. In addition, where the increase in the subject is concerned, the excess is the pronoun only and the predicate in the actual sentence if it is omitted, the appropriate verb in the sense is estimated, and omission of predicate is either to weaken, strengthen, or limit the event, or for the purpose of its mention before and the increase in shazah reading may be considered omitted in frequent reading, and vice versa.